The Effect of Benson Relaxation on Pain in Patients with Postoperative Benign Prostate Hyperplesia (BPH) at Sobirin Hospital, Kabupaten Musi Rawas - Novi Andayani; Yeni Eliyanti; Siska Ayu Ningsih (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Nursing interventions or independent actions that can be done in reducing pain in patients with BPH postoperative one of which is by teaching Benson relakasasi techniques. The research problem is that there are still many postoperative BPH patients with pain. The purpose of this study was to determine the effect of Benson's relaxation on pain in patients with postoperative benign prostatic hyperplesia (BPH) at Sobirin Hospital Musi Rawas District. This type of research is a quasi experiment. The population was 94 people and the study sample was 10 people. The type of data used in research is to use primary and secondary data. Data analysis in this study used univariate and bivariate data analysis with the t test statistic method at the 0.05 significance level. The results of this study were the average pain in patients with postoperative benign prostatic hyperplesia (BPH) before benson relaxation at Sobirin Hospital Musi Rawas District was 7.10. The average pain in patients with postoperative benign prostatic hyperplesia (BPH) after benson relaxation at Sobirin Hospital Musi Rawas District was 4.90. There is a benson relaxation effect on pain in patients with postoperative benign prostatic hyperplesia (BPH) at Sobirin Hospital Musi Rawas District with a value of p = 0,000, meaning 0.05 (α). Sobirin Hospital Musi Rawas Hospital nurses can provide non-pharmacological therapy especially Benson relaxation which can be applied as companion therapy or as part of nursing interventions in the provision of nursing care especially in patients who experience post-BPH pain.